As migrações dos jogadores brasileiros para o "império do meio" do futebol chinês - Bertrand Piraudeau (Confins)
The study of Brazilian footballers migrations to the Chinese elite championship (16 clubs studied) helps shed light on the major periods of Brazilian migration between the international space and China between 1994 and 2016. Moreover, this allows to analyse and understand the spatial and migratory interactions between the host Chinese clubs and the countries / clubs of origin of the Brazilian players and to study the place occupied by China in the globalization of transfers. This contribution shows the spatial distribution of Brazilian players playing in Chinese clubs and makes possible the understanding of China's position in the international football system. Thus, the geographical approach of the migrations of the Brazilian footballers invites, finally, to ask us about the spatial dynamics and the migratory relations created and developed by the Chinese clubs, and lived by the Brazilian players.